How does economic policy uncertainty affect corporate risk-taking? Evidence from China - Wen, Fenghua; Li, Cui; Sha, Han; Shao, Liuguo (Finance research letters, 2021)
•The empirical evidence proves the negative correlation between economic policy uncertainty and Chinese enterprise risk taking, which complements the relevant literature.•Financing constraints level in the enterprise is an essential factor adjusting the effect of EPU on corporate risk-taking. Using the firm-level data from China over the time period 2007-2018, we investigate how EPU affect the corporate risk-taking. Our empirical results show that EPU can significantly reduce the corporate risk-taking. However, such significant evidence mainly exists on the non-state-owned firms. Moreover, financing constraints level in the enterprise is an essential factor adjusting the effect of EPU on corporate risk-taking, and we find that firms with financing constraints become risk aversion in facing with EPU shocks. The conclusion of this study provides theoretical basis and practical reference for enterprises to make better decisions on high-risk and high-return investment projects.